Cortical microstructural changes and amyloid beta burden in cognitively normal subjective memory complainers: Neuroimaging / Optimal neuroimaging measures for early detection. (7th December 2020) - Chance, Steven A; Torso, Mario; Chiesa, Patrizia Andrea; Lemercier, Pablo; Vergallo, Andrea; Lista, Simone; Potier, Marie‐Claude; Habert, Marie‐Odile; Dubois, Bruno; Hampel, Harald; ,
Abstract: Background: The aim of the present study was to investigate the association between brain amyloid β (Aβ) accumulation and cortical microstructural changes in cognitively normal individuals with subjective memory complaints. Method: A total of 258 individuals (100 males, 158 females) from the Investigation of Alzheimer's Predictors in Subjective Memory Complainers (INSIGHT‐preAD) study [Dubois et al., 2018], were included. The 18F‐florbetapir PET images were used to compute whole brain and regional standard uptake value ratios (SUVr), while T1 structural and diffusion tensor imaging (DTI) scans were analysed to calculate 3 novel cortical grey matter diffusion measures (AngleR, PerpPD and ParlPD) and the mean diffusivity (MD) [McKavanagh et al., 2019]. A linear regression model was used to study the association between the global SUVr value and whole brain cortical diffusion measures, by including the diffusion measure as the dependent variable, and age, sex, APOE genotype and global amyloid SUVr as independent predictors. Partial correlation analysis, controlling for sex, was used to investigate regional associations between SUVr and diffusion values in 6 regions of interest (bilateral anterior cingulate, posterior cingulate, frontal superior orbital, inferior parietal, precuneus, middle temporal cortex). Results were considered statistically significant after false discovery rate correction (FDR <0.05). Result: Linear regression revealed that whole brain amyloid SUVr values were positively associated with whole brain AngleR (the angle between the principal diffusion direction and the radial minicolumn direction within the cortical grey matter) (β = 0.23, p <0.001). Regional partial correlations indicated significant associations between SUVr and AngleR regional values in left anterior cingulate cortex (r=0.168;p=0.010) and bilateral precuneus (left r=0.173;p=0.005; right r=0.178;p=0.004). Conclusion: These results showed a significant relationship between Aβ accumulation and cortical architectural change in subjective memory complainers. The regional associations revealed the presence of microstructural changes in key regions commonly affected in the early stage of AD [Palmqvist et al., 2017]. Our novel cortical DTI measures could offer additional information about cortical changes, playing a potential role as index of "neurodegeneration" in the ATN framework [Jack et al., 2018] of Alzheimer's biomarkers.